Sustainable development in higher engineering education: a comparative study between private and public polytechnics - Forhad, Abdur Rahman; Alam, Gazi Mahabubul; Rashid, Mamunur; Haque, Afruza; Khan, Md. Sawgat (Multidisciplinary Digital Publishing Institute, 2022)
In Bangladesh, a four-year diploma program is the highest level of technical education provided by private and public polytechnic institutions. Using representative primary data of 1372 sample sizes from Dhaka University of Engineering & Technology, Gazipur, we examined whether students graduating from private polytechnics perform worse in higher engineering education than their public school counterparts. We mainly employed a multivariate regression model and found that students from private polytechnics receive lower grades by 0.120 cumulative grade points average (CGPA) despite similar socioeconomic, academic, and demographic backgrounds. These estimated effects imply that private polytechnics fail to significantly affect sustainable engineering education. These findings suggest that policy makers increase the number of teachers and laboratory facilities for sustainable engineering education.